A bending test protocol for characterizing the mechanical performance of flexible photovoltaics - Fukuda, Kenjiro; Sun, Lulu; Du, Baocai; Takakuwa, Masahito; Wang, Jiachen; Someya, Takao; Marsal, Lluis F.; Zhou, Yinhua; Chen, Yiwang; Chen, Hongzheng; Silva, S. Ravi P.; Baran, Derya; et al. (Nature Energy, 2024)
Flexible photovoltaic (PV) devices are a promising research field with potential for wearable, portable, indoor and internet-of-things applications. Substantial progress has been made in recent years, with flexible emerging PVs reporting power conversion efficiencies (PCEs) of over 24%. Yet, there is a need for a unifying protocol to assess PV performance, compare research results, and evaluate state-of-the-art achievements in flexible PVs. Here we present a protocol for measuring PCE over 1,000 bending cycles under 1% strain. Moreover, several good practice guidelines are proposed, including those related to bending procedures, flexibility testing with and without encapsulation, and ambient conditions during testing (for example, temperature, humidity and illumination). Notably, the importance of the uniform application of the bending radius and the testing of parallel and perpendicular orientations of the bending axis with respect to the direction of the electric current are emphasized. These recommendations aim to promote consistency in device comparison and allow for better reproducibility.
CRIS-Team Scopus Importer:2024-11-01